Utilization of Wood Vinegar as Nutrient Availability Enhancer in Eggplant (Solanum melongena L.) - De Guzman, Ronel S.; Cababaro, Alben C. (Future Science / FSH-PH Publications, 2021)
The study aims to evaluate the effect of different levels of wood vinegar as a nutrient availability enhancer in eggplant. The treatments used in the study were Treatment 1 (No application of wood vinegar), Treatment 2 (0.5% of wood vinegar), Treatment 3 (0.67% of wood vinegar), and Treatment 4 (1% of wood vinegar). Based on the study results, the average height of plants showed a significant difference among the treatments. The other parameters, average growth increment, average stem diameter, average number of days to flower initiation, the average length of fruits, and an average weight of fruits, showed high significance among treatments. The result was supported by LSD that showed significant differences in control and among the treatments. Therefore, the application of Treatment 4 is the recommended ratio in eggplant production. Hence, researchable areas need to be addressed, such as evaluating the continuous use of wood vinegar in eggplant production, and challenge literature stating that wood vinegar should be stopped one week before harvesting. Additional research on time and level of wood vinegar for insect control is recommended.